Sensitivity Analysis of Calibration in the Water Evaluation and Planning (WEAP) Model for Water Resource Management in Keyang, Slahung, Sungkur Watershed - Belia Tatika Arno Dianeka; Umboro Lasminto (Journal of Civil Engineering, 2025)
Water availability is a critical issue as population growth increases, while water resources remain limited and insufficient to meet rising demand. This is evident in the Keyang, Slahung, and Sungkur sub-watersheds in Ponorogo Regency, East Java, which suffer from drought during the dry season and flooding in the rainy season. To support sustainable water resource management, accurate modelling tools are needed to reflect real field conditions. The Water Evaluation and Planning (WEAP) model is commonly used to simulate integrated water resource management, and model calibration is essential to ensure its reliability. This study employed the soil moisture method, which requires data on water availability from both surface water and groundwater, as well as water demand data across domestic, non-domestic, irrigation, and livestock sectors. Model calibration resulted in optimum parameter values: Z1 = 0, Z2 = 0, DWC = 1000, DC = 250, RRF = 10, RZC = 300, SWC = 1000, and PFD = 0.05. Based on these values, the model achieved a Nash-Sutcliffe Efficiency (NSE) of 0.85 (good category), RMSE of 5.35 (good enough), PBIAS of 19.99 (good enough), R² of 0.84 (medium influence), and MAPE of 0.42 (very accurate). These results confirm that the model reliably represents actual hydrological conditions in the study area.